2015
DOI: 10.1177/1535370215583800
|View full text |Cite
|
Sign up to set email alerts
|

Expression and promoter methylation status of hMLH1, MGMT, APC, and CDH1 genes in patients with colon adenocarcinoma

Abstract: Colorectal cancer (CRC) is the third most common cancer in men and the second in women worldwide. CRC development is the result of genetic and epigenetic alterations accumulation in the epithelial cells of colon mucosa. In the present study, DNA methylation, an epigenetic event, was evaluated in tumoral and matching normal epithelium in a cohort of 61 CRC patients. The results confirmed and expanded knowledge for the tumor suppressor genes hMLH1, MGMT, APC, and CDH1. Promoter methylation was observed for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
3
30
1
3
Order By: Relevance
“…Hyper-methylation is considered as the principle mechanism of dysfunction of tumor suppressor genes in cancer progression, moreover, promoter hyper-methylation status of some tumor suppressor genes in colon adenocarcinoma were confirmed by previous studies1112, while hydroxymethylation has been reported as an epigenetic marker whose decrease is broadly and tightly associated with cancer development131415. Since 5-hydroxymethylation in cancer research is still in infancy, further investigation is needed.…”
Section: Discussionmentioning
confidence: 77%
“…Hyper-methylation is considered as the principle mechanism of dysfunction of tumor suppressor genes in cancer progression, moreover, promoter hyper-methylation status of some tumor suppressor genes in colon adenocarcinoma were confirmed by previous studies1112, while hydroxymethylation has been reported as an epigenetic marker whose decrease is broadly and tightly associated with cancer development131415. Since 5-hydroxymethylation in cancer research is still in infancy, further investigation is needed.…”
Section: Discussionmentioning
confidence: 77%
“…SAM is required for DNA methylation. Altered DNA methylation is important in CRC (46,47). Moreover, the recent study reported that aberrant methylation was tightly related to lymph node metastasis of primary CRC (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have been conducted on HCT116 colon cancer cells to elucidate the landscape of DNA methylation [7, 8]. …”
Section: Introductionmentioning
confidence: 99%